1986
DOI: 10.1080/07399338609515725
|View full text |Cite
|
Sign up to set email alerts
|

Social and menstrual cycles: Methodological and substantive findings

Abstract: By using daily unaware, daily aware, and retrospective self-reports, this study allowed the investigation of 1) self-reports of moods and behaviors across the menstrual cycle under different conditions of awareness and type of recall, 2) social cycles for men and women, and 3) correlations between neuroticism and self-reports of moods and behaviors. Results indicate that 1) retrospective self-reports cannot be used as evidence of PMS, 2) a social cycle exists for both sexes, and 3) discrete symptomatology in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
1

Year Published

1990
1990
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
6
1
Order By: Relevance
“…The awareness effects we observed appear smaller than those reported in others studies (i.e., AuBuchon & Calhoun, 1985;Englander-Golden et al, 1986). That our sample was older and primarily nonstudents and that we excluded data from women whose cycles appeared to be anovulatory may account for this.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…The awareness effects we observed appear smaller than those reported in others studies (i.e., AuBuchon & Calhoun, 1985;Englander-Golden et al, 1986). That our sample was older and primarily nonstudents and that we excluded data from women whose cycles appeared to be anovulatory may account for this.…”
Section: Discussioncontrasting
confidence: 79%
“…AuBuchon and Calhoun (1985) found that women who were informed of the study focus reported more negative moods and physical symptoms during premenstrual and menstrual phases than did women or men who were not aware of the menstrual-cycle focus. Similarly, Englander-Golden, Sonleitner, Whitmore, and Corbley (1986) found cyclic variation for 10 of 14 mood and symptom scales in normally cycling women who knew they were participating in a menstrual-cycle study, whereas a comparable group of women who were not informed of the study focus showed cycle phase effects on only four scales, all related to physical symptoms.…”
mentioning
confidence: 90%
“…Participants' awareness of the focus of studies assessing premenstrual symptomatology has been criticized (15,40) on grounds that awareness might increase the prevalence of symptom cyclicity and thereby inflate the prevalence of PMDD. Findings in studies that have looked at this have indicated minimal (41) and some effect (42,43) of awareness. The participants in the earlier mentioned studies that used community sample (11,32) were blind to the purpose of the study and as mentioned above the prevalence of PMDD is if anything greater in their study than in our study.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly problematic because there is evidence indicating that retrospective measures of behavioral and physical symptoms are exaggerated and differ from data collected prospectively [Cook et al, 1990;Englander-Golden et al, 1985;May, 1976;Parlee, 1974Parlee, , 1982, especially if the participants believe that the menstrual cycle is the focus of the study [Aubuchon and Calhoun, 1985;Englander-Golden et al, 1978;Parlee, 1982]. Some researchers have rejected studies linking the perimenstrual phase with antisocial behaviors, believing that the observations made were simply produced as an artifact of the study's design, and that their results can be attributed to either the methods of investigation or to the subjects' expectations and attributions.…”
Section: Introductionmentioning
confidence: 99%